Effect of adaptive servo-ventilation for central sleep apnoea in systolic heart failure on muscle sympathetic nerve activity: a SERVE-HF randomised ancillary study. Issue 2 (9th February 2023) - Tamisier, Renaud; Pépin, Jean-Louis; Woehrle, Holger; Salvat, Muriel; Barone-Rochette, Gilles; Rocca, Cécile; Vettorazzi, Eik; Teschler, Helmut; Cowie, Martin; Lévy, Patrick
Background: Adaptive servo-ventilation (ASV) effectively suppresses central sleep apnoea (CSA) but has been associated with increased all-cause and cardiovascular mortality in chronic heart failure patients with reduced ventricular ejection fraction (HFrEF). All-cause and, especially, cardiovascular mortality in chronic heart failure is highly correlated with sympathetic tone. This analysis of SERVE-HF data investigated the effect of ASV on sympathetic tone in patients with HFrEF and CSA. Methods: HFrEF patients in the SERVE-HF trial (left ventricular ejection fraction (LVEF) ≤45%, apnoea–hypopnoea index (AHI) ≥15 events·h −1 with predominant CSA) were randomly assigned to receive guideline-based heart failure treatment alone (controls) or plus ASV. For this analysis, the primary outcome was change in muscle sympathetic nerve activity (MSNA) at 3-month follow-up. The effects of baseline MSNA and change in MSNA over time on mortality in the main study were also assessed. Results: 40 patients with HFrEF were included in this analysis (age 71.3±11.7 years, LVEF 34.2±7.7%, 57.5% in New York Heart Association (NYHA) Functional Class II, 42.5% in NYHA Functional Class III, AHI 35.2±11 events·h −1 ). Sympathetic tone evolution during follow-up did not differ between groups (controls: 47.6±8.3 bursts·min −1 at baseline to 44.6±11.2 bursts·min −1 ; ASV group: 43.0±9.0 bursts·min −1 at baseline to 42.74±9.45 bursts·min −1 ). The reduction in sympathetic tone was associated with significantly increased cardiovascular mortality in the ASV group, whereas in the control group reduced sympathetic tone appeared to be protective. Conclusions: Suppression of CSA with ASV did not seem to have a significant effect on chronic heart failure-related sympathetic activation. Simultaneous suppression of CSA and reduction in MSNA was associated with increased cardiovascular mortality. In patients with chronic heart failure (HF), the suppression of central sleep apnoea by adaptive servo-ventilation does not have a significant effect on chronic HF-related sympathetic activation and leads to increased cardiovascular mortality https://bit.ly/3CfoLl6